Endometriosis in ectopic pregnancy - Guzowski, Grzegorz; Palatyński, Antoni; Sieroszewski, Piotr (Menopause Review/Przegląd Menopauzalny, 2012)
Introduction : Endometriosis is defined as the occurrence of endometrial tissue outside the uterine cavity mucous membrane, which causes a chronic inflammatory reaction. Main symptoms are pelvic pain and infertility. Endometriosis can cause damage to the fallopian tubes and ovaries as a result of inflammation and scarring. The main issue of this paper is estimation whether endometriosis can lead to ectopic pregnancy. Materials and methods : Research was conducted in 1997-2006 on 115 patients with ectopic pregnancy located in the fallopian tube. In those women during laparoscopy endometriosis genitalis externa was identified. All patients were treated hormonally, and then laparoscopy was performed again. Results : In 70 patients, endometriosis was diagnosed when performing surgery on the fallopian tube to remove the ectopic pregnancy, in 45 patients, endometriosis was diagnosed 1-3 years after a history of ectopic pregnancy, during a subsequent laparoscopy. After removal of ectopic pregnancy and completed hormonal treatment, within 1-3.5 years, out of a total of 115 patients, 74 got pregnant. Women with stuffy fallopian tubes were referred to IVF. Conclusion: 1. During removal of ectopic pregnancy, identification of endometriosis needs another treatment of this illness. 2. Fertility of women who were treated because of endometriosis is high and accounts for 64% of intrauterine full-term pregnancies in the study group.